COVID-19 mortality in patients with immunodeficiency and its predictors: a systematic review - SeyedAhmad SeyedAlinaghi; Amirali Karimi; Alireza Barzegary; Hengameh Mojdeganlou; Farzin Vahedi; Seyed Peyman Mirghaderi; Parnian Shobeiri; Maryam Ramezani; Parisa Yousefi Konjdar; Pegah Mirzapour; Marcarious M. Tantuoyir; Esmaeil Mehraeen; et al. (European Journal of Medical Research, 2022)
Abstract Introduction Patients with immunodeficiency are usually more prone to worse outcomes of infectious diseases. However, there are some disagreements in the context of COVID-19, for example, in patients with human immunodeficiency virus (HIV). Herein, we aimed to systematically review the risk and predictors of COVID-19 mortality in people with primary or secondary immunodeficiency. Methods PubMed, Scopus, Web of Science, and Science Direct were searched. We followed a two-step screening process to identify eligible results. We first reviewed the title and abstract of the records and the unqualified studies were removed. Then, their full texts were evaluated based on their coherence with the purpose and inclusion/exclusion criteria, and those eligible for qualitative synthesis were included. Results Twenty-two articles were included, which investigated a total of 109,326 with primary or secondary immunodeficiencies. Three studies investigated the pediatric and infant population, while other studies were conducted on the adult population. Overall, studies on both primary and secondary immunodeficiency conflicted as some reported higher and some mentioned lower mortality rates in patients with immunodeficiency. Conclusions Overall, there were two points of view in both types of immunodeficiencies. The first is the classical viewpoint that all immunodeficient patients are at a higher risk of infection leading to a higher mortality rate. The second types of studies found that immunodeficiency might play a less important or even an inverse role in mortality rates by lowering the severity of the inflammatory response. However, it is important to take note to comorbidities, such as DM, HTN, CAD, ESRD, history of lower respiratory infection, etc., and demographic factors, such as obesity and age > 70 years, as they appear to influence the mortality rate, especially in patients with secondary immunodeficiency.